THE CORRUPTION TRENDS WITHIN THE ASEAN COUNTRIES: A BIBLIOMETRIC ANALYSIS REVIEW - Muliani, Muliani; Sayuti, Alfian; Septian, Defel (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
This article gives a quantitative examination of corruption trends in one of the ASEAN countries. The study focused on 5 research questions. Information is collected to check the above research questions and a network map is applied. This study aims to examine the publication of documents based on the most influential articles, co-authorship of country, co-occurrenceance of all keywords, most cited sources, co-citation of cite author. Keywords are categorized into several clusters. The type of analysis used is bibliometric analysis. This study took the latest data of 823 articles from the scientific database, namely SCOPUS from 2000-2024, and network analysis using VOSviewer software. This study found that The most influential article in the study of Corruption in ASEAN Country is the article entitled "Institutional causes, macroeconomic symptoms: Volatility, crises, and growth" with a number of citations of 785 times. Indonesia is the ASEAN state that contributes the most to research related to Corruption with a total of 279 documents. The main field of study keywords that are most often used in Corruption research in ASEAN Country are Corruption. The journal source that publishes the most research on corruption is the Journal of Financial Crime with a total of 621 citations. Based on the co-citation of cite author, Shliefier is the author with the most citations. This research has certain limitations and is concluded by providing implications and suggestions for future studies. Finally, this study will provide more insight for researchers, academics, and others to find research gaps in the field of corruption.